2015
DOI: 10.1159/000430404
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibition by Oxaliplatin, a Platinum-Based Anti-Neoplastic Agent, of the Activity of Intermediate-Conductance Ca2+-Activated K+ Channels in Human Glioma Cells

Abstract: Oxaliplatin (OXAL) is a third-generation organoplatinum which is effective against advanced cancer cells including glioma cells. How this agent and other related compounds interacts with ion channels in glioma cells is poorly understood. OXAL (100 µM) suppressed the amplitude of whole-cell K+ currents (IK); and, either DCEBIO or ionomycin significantly reversed OXAL-mediated inhibition of IK in human 13-06-MG glioma cells. In OXAL-treated cells, TRAM-34 did not suppress IK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 43 publications
3
23
0
Order By: Relevance
“…The single-channel conductance of IK Ca channels in U373 cells was calculated to be 32 pS, a value similar to the prototypical IK Ca channels present in other types of cells [10,11,13,26], but apparently less than that of BK Ca channels [9,27]. Moreover, clotrimazole and TRAM-34 inhibited, but chlorzoxazone and 1-EBIO stimulated the activity of these channels in U373 cells.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The single-channel conductance of IK Ca channels in U373 cells was calculated to be 32 pS, a value similar to the prototypical IK Ca channels present in other types of cells [10,11,13,26], but apparently less than that of BK Ca channels [9,27]. Moreover, clotrimazole and TRAM-34 inhibited, but chlorzoxazone and 1-EBIO stimulated the activity of these channels in U373 cells.…”
Section: Discussionmentioning
confidence: 59%
“…To determine whether the inhibitory effect of TMZ on I K in U373 cells can be shared by the regulators of IK Ca channels, the effects of clotrimazole, TRAM-34, and TRAM-34 plus ionomycin were also investigated. Clotrimazole and TRAM-34 are potent inhibitors of IK Ca channels, whereas ionomycin is a Ca 2+ ionophore [10,12,13]. At −100 mV, the I K amplitude …”
Section: Changes In I K Amplitude In Tmz-treated U373 Cellsmentioning
confidence: 99%
“…No notable difference in single‐channel conductance of BK Ca channels was demonstrated (189 ± 11 pS [control] vs. 193 ± 12 pS [30 μM compound #326], n = 11, p > 0.05). However, the activity of IK Ca channels in these cells (Huang et al, ; Yeh et al, ) was not subject to stimulation by compound #326 (30 μM). Similar to the observations made earlier, compound #326 at a concentration of 30 μM was effective at stimulating BK Ca channels found in glioma cells.…”
Section: Resultsmentioning
confidence: 94%
“…Because I K(Ca) present in GH 3 cells may be different from that in other types of cells, the effect of compound #326 in 13‐06‐MG glioma cells was also examined. Previous observations in our laboratory have demonstrated that these glioma cells express BK Ca channels that are sensitive to inhibition by paxilline, another indole diterpene structurally similar to verruculogen (Huang et al, ). Therefore, in a final set of experiments, we investigated effects of this compound on the activity of single BK Ca channels in 13‐06‐MG glioma cells.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation